The Effect of Resistance Training on Serum Levels of Adipokine and Inflammatory Markers of Cardiovascular Disease in Obese Men - Mohsen Akbarpour (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2013)
Background and Objectives: Recent studies on endocrine function have revealed many pathological complications in relation to obesity and metabolic diseases. Thus, the present study was carried out with the aim of investigating the effect of 12-week resistance training on the serum levels adipokine (adiponectin and leptin) and inflammatory markers of cardiovascular diseases in obese men. Methods: In this semi-experimental study, 20 non-athlete obese men were randomly assigned to two groups of experimental and control. The experimental group performed the resistance training protocol, three sessions per week for 12 weeks, while the control group was prohibited to do training program during the research implementation. Five ml of venous blood was taken from the participants at the beginning of the sixth week and at the end of the twelfth week to measure leptin, adiponectin, CRP, IL-6, and TNF-α. The significance level was considered to be >α0.05. Results: Resistance training caused decrease in CRP (p=0.002), IL-6 (p=0.001) and leptin (p=0.002), and increase in adiponectin (p=0.001) in the experimental group compared to the control group. Also, TNF-α level showed a decrease in the experimental group after 12 weeks of resistance training, which was not statically significant. Conclusion: The results of this study showed that regular resistance trainings reduce the potential risk of cardiovascular diseases via improvement of the plasma levels of adiponectin, leptin, CRP, and IL-6, and it can be used as an effective nonpharmacological treatment to prevent these diseases.